2022
DOI: 10.1101/2022.01.11.22268884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Educational attainment, health outcomes and mortality: a within-sibship Mendelian randomization study

Abstract: Previous Mendelian randomization (MR) studies using population samples (population-MR) have provided evidence for beneficial effects of educational attainment on health outcomes in adulthood. However, estimates from these studies may have been susceptible to bias from population stratification, assortative mating and indirect genetic effects due to unadjusted parental genotypes. Mendelian randomization using genetic association estimates derived from within-sibship models (within-sibship MR) can avoid these po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…2. The use of covariates for additional exploratory purposes was considered [38][39][40] (online suppl. Table S1, S2; for all online suppl.…”
Section: Participantsmentioning
confidence: 99%
“…2. The use of covariates for additional exploratory purposes was considered [38][39][40] (online suppl. Table S1, S2; for all online suppl.…”
Section: Participantsmentioning
confidence: 99%
“…Moreover, among individuals with college degrees, those with a higher education polygenic score exhibited a lower likelihood of obesity than those with a relatively lower education polygenic score. Howe et al [ 28 ] conducted a within-sibship MR study that revealed a strong association between higher EA and lower BMI. Furthermore, in an observational study, Panchal et al [ 29 ] found that individuals with lower EA (less than college graduates) had higher BMI than those with higher EA (college graduates and post-college degrees) [31.8 ± 6.4 vs. 29.6 ± 4.8 vs. 29.7 ± 5.2, p = 0.04].…”
Section: Discussionmentioning
confidence: 99%
“…MRlap(23) was employed to correct the sample overlap and is a method to approximate the sample overlap using cross-trait LD-score regression (LDSC). It has been used in many studies for MR analysis(24, 25, 26, 27, 28). The detailed descriptions of all the MR approaches are given in the Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%